17 'Planning for a future I didn't know I'd have'; a communication tool to find out what matters most to people with cystic fibrosis. (14th March 2023) - Curtis, Polly; Bundy, Laura; Oliver, Claire; Patel, Kathryn; Varkonyi-Sepp, Judit; Davis, Carol; Nightingale, Julia
Abstract : Background: University Hospital Southampton's Hospital Supportive and Palliative Care Team has collaborated with the Regional Adult Cystic Fibrosis (CF) team to improve opportunities for people with CF (PWCF) to discuss what matters most to them. In July 2022 we implemented a communication tool, 'the Bubbles', offering PWCF the opportunity to open conversations about tricky topics including treatments and the future. We have assessed the impact of this change in practice. Method: A multidisciplinary working group developed a communication tool using quality improvement (QI) methodology, to promote shared decision making and honest conversations with adult PWCF. Initial ideas were shared with PWCF to refine the topics included. The tool was then offered to 40 consecutive PWCF in clinic. Feedback was requested at the clinic with mixed qualitative and quantitative elements to explore patient experience. Results: The mean age of participants was 31. 60% were female. Mean forced expiratory volume in 1 second was 81% predicted. 93% of patients gave feedback. 40% identified areas to discuss; of these, 13 participants identified multiple topics. 7/40 participants taking part were not prescribed a CF disease modifying drug; these PWCF did not identify areas for discussion. 75% rated the Bubbles as useful or very useful. The Bubbles made topics easier to talk about for 30 PWCF. The most common themes included confidence/self-esteem, anxiety/stress, finances, sleep and planning for the future. The chosen topics were unexpected with a strong focus on psychosocial domains. Conclusion: The Bubbles communication tool was positively evaluated by PWCF, resulting in multiple opportunities for wide ranging discussions and improved patient experience. There is potential for adaptation of the tool to aid its use for patients with learning disabilities or other diseases. The CF team are modifying their MDT processes to incorporate these discussions into practice as part of an ongoing QI project.